Imaging Recommendations for Diagnosis, Staging, and Management of Carcinoma of Unknown Origin (Lymph Node, Pulmonary, Liver, Skeletal, and Brain) with Emphasis on the Current Position of PET-CT in Carcinoma of Unknown Origin (CUP) - Loharkar, Sarvesh; Basu, Sandip (Indian Journal of Medical and Paediatric Oncology, 2023)
Most of the established guidelines mention and recommend the use of FDG-PET/CT (fluorodeoxyglucose positron emission tomography/computed tomography) in carcinoma of unknown primary (CUP) especially in head–neck squamous cell carcinoma; as described in this article, this forms a powerful one-stop shop in diagnosing and staging modality and has multiple applications in difficult situations of CUPs. Although not used as a screening modality, FDG-PET/CT is recommended as the primary imaging modality in the evaluation of primary, staging, and response evaluation for CUP with histology known to demonstrate FDG avidity, especially patients presenting with lymph nodal disease. It should be remembered that many histological types do not concentrate on FDG and FDG also shows false-positive results in many other conditions like infection-inflammation; however, at the same time, it delivers high negative predictive values, an important consideration when employing FDG-PET/CT in the CUP scenario. SSTR-based PET/CT plays a pivotal role in primary diagnosis, staging, therapy planning, and response assessment in CUPs with neuroendocrine tumor or neuroendocrine neoplasm histology. The last two decades has witnessed great advancement in PET instrumentation and radiopharmaceuticals: particularly techniques like PET/magnetic resonance imaging and radiopharmaceuticals like FAPI (fibroblast-activation protein inhibitor)-based PET tracers. Hence, the role of PET/CT is expected to expand its reach in the coming years in line with accruing literature evidence, thereby upgrading its role and reliability in oncological practice strategies.
Keywords: USG; PET; PET-CT; FDG; FNAC; biopsy; carcinoma of unknown primary (CUP)